Crop responses to furrow diking in North Carolina. Issue 5 (16th September 2014) - Foote, William; Nuti, Russell; Edmisten, Keith; Jordan, David L.; Wells, Randy; Fisher, Loren
Abstract : Furrow diking is the practice of installing earthen dams to form small basins between crop rows to reduce water runoff and improve water retention. It has been used extensively in the southern Great Plains but research evaluating crop response to furrow diking is limited in North Carolina and other southeastern states. Experiments were conducted to determine cotton, peanut, and corn yields following furrow diking in conventional and strip tillage systems. Earn 1 CEU in Soil & Water Management by reading this article and completing the quiz at www.certifiedcropadviser.org/certifications/self‐study/677 .